Wastewater Pond Design and Construction - Powell, G. Morgan; Dallemand, Barbara; Mayo, Ann (My University, 1998)
This publication presents design and construction information about wastewater ponds for sanitarians, contractors, owners, and others.
MF1044_1998_08
Keywords: MF1044; Equipment and Structures; Health and Safety; Water; MF